Juegos educativos como estrategias didácticas, para potenciar el aprendizaje de las matemáticas en el módulo 4. estudiar y jugar me hacen crecer en los niños y niñas de cuarto grado de la escuela centro educativo comunitario de educación básica intercultural bilingüe “Huayna Capac”, de la comunidad de Nuevo Porvenir, parroquia La Paz, cantón Yacuambi provincia de Zamora Chinchipe. Periodo académico 2014-2015 - Guamán Lozano, Luis Leonardo (2015)
This research titled: such as educational games teaching strategies, to Enhance learning of mathematics in the study and play MODULE 4. MAKE ME GROW IN FOURTH GRADE SCHOOL CHILDREN OF COMMUNITY EDUCATION CENTER INTERCULTURAL BILINGUAL EDUCATION BASIC "Huayna Capac" NEW FUTURE COMMUNITY OF PEACE PARISH , Yacuambi Canton province of Zamora Chinchipe. 2014-2015 academic year, "Whose overall objective is to Develop Strategies to Enhance the educational game for children in the fourth grade of General Basic Education in the area of mathematics, in Module 4 Studying and playing make me grow. This research is descriptive and quasi-experimental, in Which the methods, comprehensive, analytical, synthetic, participatory diagnosis, proactive model or, for workshops and comprehensive evaluation, with the technique of direct observation and conducting Were used to survey for teachers and students, so get Timely information for the development of research, RESULTING in students know the concept of educational games, games do not work or produces written materials, visual or auditory, teaching does not propose educational games in your daily schedule and do not use materials That meet in the middle. In the research work nine intervened human talents, one teacher and eight students, we close up commercial That the application of teaching strategies to Enhance learning of mathematics, it is essential to Develop creativity and critical analysis of the students and help THUS Their comprehensive training in learning.